2010
DOI: 10.4322/rbpv.01901010
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da infecÇão crônica por Toxoplasma gondii sobre a parede intestinal de gatos domésticos

Abstract: ResumoO objetivo deste trabalho foi analisar os efeitos da infecção causada pelo Toxoplasma gondii sobre a parede do duodeno de gatos. Foram utilizados seis gatos (Felis catus), com cerca de três meses de vida, distribuídos aleatoriamente em Grupo controle (G1; n = 3) e Grupo infectado (G2; n = 3). Os animais do G2 receberam, por via oral, 200 cistos teciduais da cepa ME49 (tipo II) do T. gondii. Após 40 dias, os animais foram submetidos à eutanásia, laparotomia e retirada do duodeno, que foi fixado em solução… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Besides, studies reported changes in the intestinal wall of infected animals (Shiraishi et al 2009, Bonapaz et al 2010, Da Silva et al 2010a, possibly because the digestive tube is the route of entry of T. gondii (Weiss and kim 2007). Such changes indicate the both digestion and absorption may be compromised, even in animals showing no clinical signs of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, studies reported changes in the intestinal wall of infected animals (Shiraishi et al 2009, Bonapaz et al 2010, Da Silva et al 2010a, possibly because the digestive tube is the route of entry of T. gondii (Weiss and kim 2007). Such changes indicate the both digestion and absorption may be compromised, even in animals showing no clinical signs of infection.…”
Section: Introductionmentioning
confidence: 99%